ISOLASI DAN UJI AKTIVITAS ANTIBAKTERI MINYAK ATSIRI DARI RIMPANG LENGKUAS (Alpinia galanga L.) - I M. Oka Adi Parwata; P. Fanny Sastra Dewi (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2008)
Isolation and antibacterial activity test of the languas rhizomes (Alpinia galanga L.) essential oil was carriedout The extract was yellow in colour with a volume of 3,5 mL.The activity test on E. coli bacteria at concentrations 100 ppm and 1000 ppm showed a retardation area of 7mm and 9 mm in diameters. At 1000 ppm it retarded S. aureus bacteria to a diameter of 7 mm. Gas Chromatography– Mass Spectrometer data show that the essential oil of the languas rhizomes contains mainly 8 components : Dlimonen;Eukaliptol; 3-sikloheksen-1-ol, 4-metil-1-(1-metietil); Fenol, 4-(2-profenil)-asetat; 2,6-oktadien-1-ol, 3,7-dimetil-asetat; 1,6,10-dodekatrien, 7,11-dimetil-3-metilen; Pentadesen; sikloheksen, 1-metil-4-(5-metil-1-metilen-4-heksenil.